Study of the effect of an acid treatment of a natural Moroccan bentonite on its physicochemical and adsorption properties - Daou, Ikram (Water science and technology : a journal of the International Association on Water Pollution Research, 2017)
In this study, a natural bentonite taken from a deposit in the Northeast of Morocco has been purified (PB) and treated with various HCl molarities (xHPB) in order to obtain an HCl/Bentonite weight ratio equal to 0.2, 0.4 and 0.6. The obtained physicochemical characterization results indicated that the PB sample is composed mainly of the montmorillonite phase. The impact of acid treatment was investigated by identifying changes in the chemical composition, cation exchange capacity, infrared absorption bands, crystalline structure, morphology of the particles and specific surface area. The adsorption behavior of methylene blue (MB) and methyl orange (MO) in aqueous solution onto PB and xHPB samples was investigated by varying the initial concentration of dyes, the contact time and the temperature. The obtained results showed that the experimental data best fit the Langmuir model and the pseudo-second-order kinetic model. X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) studies carried out after MB and MO adsorption onto PB samples indicated that MB cations were intercalated, in the form of monomers and dimers, with a large amount of monomers, slightly tilted against the plane of the clay surface. While MO molecules adsorb, with a near perpendicular alignment, with their SO3- group and O- atoms facing the mineral surface plane